THE FEATURES OF СONSTITUTIONALISM IN THE STATES OF ANCIENT MESOPOTAMIA AND THE REPUBLIC OF ROME - Machovenko, Jevgenij (Teisė, 2016)
Analysis of the historical legal monuments of Mesopotamia and Rome shows that there were meaningful features of constitutionalism (in its today’s meaning) in Ancient world, including the constitution and the constitutional justice. Therefore the research of the history of constitutionalism has to cover the times when the first known legal acts were drafted until present and the division of the pre-history of the constitutionalism (till the first wave of constitutions in 2nd half of 18th century) and the history of the constitutionalism provided in academic literature is groundless. The constitution existed as the whole of written and unwritten provisions in the states of Ancient Mesopotamia and the Republic of Rome and it was interpreted first of all as the expression and standard of justice and the hierarchy of values, the “nucleus” or “pivot” of law and all legal norms were turning around this “pivot”. In the Republic of Rome the mandatory decision of the augurs’ councils, taken on the ground of applications of the officers or institutions, or the obligation of the officers or institutions to void the legal acts or elections that augurs founded unconstitutional look very modern. The history of constitutionalism is the continuous both qualitative and quantitative grow of constitutionalism, that has its inner logic and is subject to certain principles. Therefore, ancient constitutions and the expressions of constitutionalism have the connection with actual constitutions, constitutional justice and etc.